Formulation And Evaluation Of Sunscreen Spray Gel Preparations From Kepok Banana Flower Extract (Musa Acuminata X M. Balbisiana) With Variations In Extract Concentration Based On SPF Value - Natasya Putri Handayani; Rahmat Hidayat; Alfina Nurrahman (International Journal of Health Engineering and Technology, 2026)
UV exposure causes skin damage such as erythema and premature aging, so natural sunscreens are needed such as ethanol extract of kepok banana flowers (Musa acuminata × M. balbisiana) which are rich in flavonoids and polyphenols. The aim of this study was to determine the effect of variations in extract concentration (0.8%, 1%, 1.2%) on the physical characteristics and SPF value of spray gel. This type of descriptive experimental study used the maceration method, formulation with carbopol 940, and in vitro evaluation. The extract population was from Pontianak, samples of three formulas with three replications. Instruments used were UV-Vis spectrophotometer, Brookfield viscometer; ANOVA analysis and linear regression. The results showed pH 5.64-6.25, viscosity 989-1915 cPs, homogeneous, SPF 15.90 (F1) to 18.76 (F3). Conclusion: A concentration of 1.2% is optimal for effective and stable sunscreen spray gel.